Role of preoperative x-ray endovascular interventions for improvement of resectability of colorectal liver metastases - P. G. Tarazov; D. A. Granov; A. A. Polikarpov; V. I. Sergeev; A. V. Kozlov; А. S. Polekhin; A. V. Moiseenko; Е. V. Rozengauz (Вестник хирургии имени И.И. Грекова)
The objective was of the study to evaluate the role of preoperative x-ray endovascular interventions – transcatheter arterial chemoembolization (TACE) and portal vein embolization (PVE) – for improvement of resectability of colorectal liver metastases.Material and methods. Between 1997 and 2017, we treated 11 patients who simultaneously had large-volume (60–70 %) of right liver lobe colorectal metastases and small future remnant liver. The treatment was started from 1–4 cycles of TACE to reduce or stabilize the rapid growth of the tumor. In case of good effect, we performed PVE and then we performed liver resection.Results. There were no major complications of TACE or PVE. After 1–4 cycles of TACE, the volume of metastases showed partial decrease or stabilization. The following PVE allowed to increase the future remnant volume of the left liver lobe up to a safe 40–45 %. Right – sided hemihepatectomy was performed in 6 patients and extended right-sided hemihepatectomy in 5 patients. There were no postoperative mortality or severe complications. At present, 4 patients are alive without recurrence during 1.5–8 years, and 4 other patients received endovascular treatment for local recurrence are alive during 1.5–5 years. The 3 patients died from tumor progression during 13–30 months. CONCLUSION. In patients with simultaneously extensive for resection volume of right liver lobe metastases and small left liver lobe, the primary treatment with TACE is reasonable. Only after the documentation of tumor decrease or stabilization, it is necessary to determine the timing of PVE and following major liver resection. This order of treatment procedures allows to improve resectability in cases with extensive, large-volume, rapidly grown malignant liver lesions.